The combined effect of a novel formula of herbal extracts on bacterial infection and immune response in Micropterus salmoides - Guo, Huanyu; Chen, Jing; Yuan, Xuemei; Zhang, Jian; Wang, Jiayang; Yao, Jiayun; Ge, Haixia (Frontiers in Microbiology, 2023)
Herbal extracts have been considered as ideal alternative to antibiotics in aquaculture and application of combinatory effective extracts always can exhibit the enhanced bioactivity with high efficiency. In our study, a novel herbal extract combination GF-7, which is composed of Galla Chinensis, Mangosteen Shell extracts as well as the effective parts of Pomegranate peel and Scutellaria baicalensis Georgi extracts, was prepared and applied for the therapy of bacterial infection in aquaculture. The HPLC analysis of GF-7 was also investigated for quality control and chemical identification. In the bioassay GF-7 had excellent antibacterial activity against various aquatic pathogenic bacteria in vitro, and the related MIC values were between 0.045 and 0.36 mg/mL. After feeding Micropterus salmoide with GF-7 (0.1%, 0.3% and 0.6% respectively) for 28 days, the activities of ACP, AKP, LZM, SOD and CAT of the liver in each treatment group were significantly increased and the content of MDA was significantly decreased. Meanwhile, the hepatic expression of the immune regulators including IL-1β, TNF-α and Myd88 at different times was up-regulated in varying degrees. The challenge results exhibited a good dose-dependent protective effect on M. salmoides infected with A. hydrophila, which was further confirmed by liver histopathology. Our results imply that the novel combination GF-7 is a potential natural medicine for prevention and treatment of numerous aquatic pathogenic infectious diseases in aquaculture.